PyCCE: A Python Package for Cluster Correlation Expansion Simulations of Spin Qubit Dynamics. Issue 11 (3rd October 2021) - Onizhuk, Mykyta; Galli, Giulia
Abstract: PyCCE, an open‐source Python library for simulating the dynamics of spin qubits in a spin bath, is presented using the cluster‐correlation expansion (CCE) method. PyCCE includes modules to generate realistic spin baths, employing coupling parameters computed from first principles with electronic structure codes, and enables the user to run simulations with either the conventional or generalized CCE method. Three use cases of the Python library are illustrated: the calculation of the Hahn‐echo coherence time of the nitrogen‐vacancy in diamond; the calculation of the coherence time of the basal divacancy in silicon carbide at avoided crossings; and the calculation for magnetic field orientation‐dependent dynamics of a shallow donor in silicon. The complete documentation, downloadable tutorials, and installation instructions are available at https://pycce.readthedocs.io/en/latest/ . Abstract : PyCCE, an open‐source Python library to simulate the dynamics of a spin qubit interacting with a spin bath, using the cluster‐correlation expansion, is presented.